The Role of Educational Psychology in Driving Digital Transformation in Islamic Boarding Schools: Integrating Traditional Values ​​with Technological Innovation - Sofiyyudin Azka; Abdul Muhid (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Digital transformation in Islamic boarding schools has become an urgent need amidst the rapid development of information technology. This study aims to explore the role of educational psychology in managing digital transformation in Islamic boarding schools, how technology can be integrated with traditional Islamic values, and the urgency of the role of educational psychology in managing digital transformation. Using library research methods, this article refers to various sources such as books, journals, scientific articles, and literature. Educational psychology plays a role in ensuring that the technology used can strengthen traditional Islamic values ​​that are the foundation of education in Islamic boarding schools. Thus, the integration of technology not only increases the effectiveness and efficiency of learning, but also maintains and enriches the values ​​and traditions of Islamic boarding schools. Through a wise and inclusive approach, Islamic boarding schools can develop a modern and relevant learning environment with the times, while remaining firmly rooted in Islamic values.